Emergent Shared Intentions Support Coordination During Collective Musical Improvisations. Issue 1 (12th January 2021) - Goupil, Louise; Wolf, Thomas; Saint‐Germier, Pierre; Aucouturier, Jean‐Julien; Canonne, Clément
Abstract: Human interactions are often improvised rather than scripted, which suggests that efficient coordination can emerge even when collective plans are largely underspecified. One possibility is that such forms of coordination primarily rely on mutual influences between interactive partners, and on perception–action couplings such as entrainment or mimicry. Yet some forms of improvised joint actions appear difficult to explain solely by appealing to these emergent mechanisms. Here, we focus on collective free improvisation, a form of highly unplanned creative practice where both agents' subjective reports and the complexity of their interactions suggest that shared intentions may sometimes emerge to support coordination during the course of the improvisation, even in the absence of verbal communication. In four experiments, we show that shared intentions spontaneously emerge during collective musical improvisations, and that they foster coordination on multiple levels, over and beyond the mere influence of shared information. We also show that musicians deploy communicative strategies to manifest and propagate their intentions within the group, and that this predicts better coordination. Overall, our results suggest that improvised and scripted joint actions are more continuous with one another than it first seems, and that they differ merely in the extent to which they rely on emergent or planned coordination mechanisms.